The role of nitric oxide and reactive oxygen species in the positive inotropic response to mechanical stretch in the mammalian myocardium. - Zhang, Y; Dingle, L; Hall, R; Casadei, B (2009)
The endothelial nitric oxide synthase (eNOS) has been implicated in the rapid (Frank-Starling) and slow (Anrep) cardiac response to stretch. Our work and that of others have demonstrated that a neuronal nitric oxide synthase (nNOS) localized to the myocardium plays an important role in the regulation of cardiac function and calcium handling. However, the effect of nNOS on the myocardial response to stretch has yet to be investigated. Recent evidence suggests that the stretch-induced release of angiotensin II (Ang II) and endothelin 1 (ET-1) stimulates myocardial superoxide production from NADPH oxidases which, in turn, contributes to the Anrep effect. nNOS has also been shown to regulate the production of myocardial superoxide, suggesting that this isoform may influence the cardiac response to stretch or ET-1 by altering the NO-redox balance in the myocardium. Here we show that the increase in left ventricular (LV) myocyte shortening in response to the application of ET-1 (10 nM, 5 min) did not differ between nNOS(-/-) mice and their wild type littermates (nNOS(+/+)). Pre-incubating LV myocytes with the NADPH oxidase inhibitor, apocynin (100 microM, 30 min), reduced cell shortening in nNOS(-/-) myocytes only but prevented the positive inotropic effects of ET-1 in both groups. Superoxide production (O(2)(-)) was enhanced in nNOS(-/-) myocytes compared to nNOS(+/+); however, this difference was abolished by pre-incubation with apocynin. There was no detectable increase in O(2)(-) production in ET-1 pre-treated LV myocytes. Inhibition of protein kinase C (chelerythrine, 1 microM) did not affect cell shortening in either group, however, protein kinase A inhibitor, PKI (2 microM), significantly reduced the positive inotropic effects of ET-1 in both nNOS(+/+) and nNOS(-/-) myocytes. Taken together, our findings show that the positive inotropic effect of ET-1 in murine LV myocytes is independent of nNOS but requires NADPH oxidases and protein kinase A (PKA)-dependent signaling. These results may further our understanding of the signaling pathways involved in the myocardial inotropic response to stretch.